Delay Separated Neural Network Inverse Control in Main-Steam Temperature System - Lingfang Sun; Yihang Li; Dan Li (Institute of Advanced Engineering and Science, 2014)
In order to improve the control effect of the main steam temperature with large time delay , this paper proposed a delay separated neural network inverse (DSNNI) control scheme. We got the delay time and the positive model without delay by using adaptive linear element and BP network. Then we made the neural network inverse model of the positive model without delay. An appropriate reference model was selected to make the inverse model’s output smoothing. It is an open-loop control system when the model is cascaded into original system. It will avoid the instability caused by the closed-loop control systems. Off-line identification and on-line identification are combined to get the inverse model in order to reduce the steady-state error and make the system have fine adaptive capacity. Detail simulation tests are carried out on the given 300MW power unit. Tests show that the neural network inverse control with delay time separation can get rapid and smooth output for the main steam temperature system. It is able to overcome the adverse effects caused by the time delay and the parameters changes. Compared with the cascade PID controller, it has faster response, better robustness and anti-interference performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4674